An analysis of variations in body movement difficulty of 2016 Olympic Games rhythmic gymnast candidates - AGOPYAN, ANİ (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
The aim of this study was to determine the use and the variety of body movement difficulty in the routines of individual rhythmic gymnasts aiming to compete in the 2016-Olympic Games, both those who qualified and those who did not. The research data was collected from the routines of 24 rhythmic gymnasts, from a total of 96 videos that were recorded during an Olympic qualification competition for the 34(th) Rhythmic Gymnastics World Championships of 2015 in Stuttgart/Germany. The gymnasts were divided into G(1)1-15, the top 15 gymnasts, and G(2)16-24, the remaining 9 gymnasts. The number of body movements (jumps/leaps, balances and rotations) and their comparative execution difficulty values were examined by quality and quantity. Penche rotation on a flat foot (79.2%), a jete with a turn jump (66.67%) and balancing with a high back scale leg (57.29%) were the most frequently used body movements. The preferences of G(1) gymnasts over G(2) gymnasts for different types of static and dynamic difficulties across different movements even where there was not a wide variety. Rhythmic gymnasts at different performance levels generally tend to use the same body movement difficulties for all of their routines and this clearly indicates a lack of body difficulty variation.
Keywords: Rhythmic gymnastics; video analysis; individual routine; body movement difficulty; APPARATUS DIFFICULTY; GROUP COMPETITION; PERFORMANCE; ROUTINES